High BNP level as risk factor for acute kidney injury and predictor of all-cause mortality in STEMI patients - Akgul, O.; Uyarel, H.; Pusuroglu, H.; Isiksacan, N.; Turen, S.; Erturk, M.; Surgit, O.; Celik, O.; Oner, E.; Birant, A.; Akturk, I. F.; Uslu, N. (My University, 2014)
The aim of this study was to evaluate the predictive value of brain natriuretic peptide (BNP) in the development of acute kidney injury (AKI) and 6-month all-cause mortality after primary percutaneous coronary intervention (PCI) for ST-elevation myocardial infarction (STEMI) in a modest-risk population.